Superior College Applied Research Competence of SPI Members in the Context of Improving the Quality of Supervisory Performance at Manado State University - Michael Miran; Olviane Sumampouw (Pandawan, 2023)
According to Regulation of the Minister of Education and Culture Number 22 of 2017, Internal Supervision within the Ministry of Education and Culture has the task and function of assisting the Head of the Work Unit in carrying out internal supervision by performing the functions of preparing supervision programs, supervising policies and programs, supervising the management of personnel, finances, and state property, monitoring, and coordinating the follow-up of internal supervision activities. Descriptive analysis was used in conjunction with qualitative research methodologies for this study. As a consequence of speaking with 6 (six) SPI Members at Manado State University, we may deduce the following: 1) Skills required to complete SPI Tasks 2) The percentage of members with expertise in law, finance, and technology 3) To increase the competency of SPI members, ongoing training is required. 4) Do leadership skills effectively assist performance achievement? 5) Recognizing and praising each 6) Should there be selection during the recruitment of SPI members? If so, what kind of selection stages should be used?